Clínica psicológica antirracista: uma nova episteme para uma psicologia brasileira decolonial. - Costa, Maria Conceição (2022)
This thesis seeks to problematize the psychological clinic in an intersectional perspective, wanting to understand the limits and possibilities of this clinic for the reception of black people who reported racism in their narratives. Specifically, it is intended to understand how the construction process of Brazilian racism would rebound in the psychological clinic; describe anti-racist theories and practices in psychological clinic; understand the ways in which the psychological clinic contemplates racialized voices. The proposed objectives were directed to reflect on the construction process of Brazilian structural racism, which required an intersectional posture, given that this racism expressed its profoundly discriminatory aspect, which caused the separation of Brazilian society, placing black people in the condition of subaltern and privileged white people. Consequently, racialized constructions and subjective positions of the black population and racists of the white population are encouraged, which defined the place and non-place of the subjects. As a methodological path, we used narrative interviews with 6 black women, three patients/clients and three therapists (also black women) from which we mapped their trajectories, seeking to analyze their situations of clinical experiences, not successful for clients/patients, due to their color and how they were possible for the therapists. The cartographic route thought as a “walk” allowed mapping the processes of experiences of racism in a perspective of studies of coloniality, intersectionality and decolonial process. More than a method, a cartographic positioning guided us in the way of carrying out the research, understanding this process as the formulation of an interventional research. This study may contribute to the construction of propositions that allow the characterization of an ethical-aesthetic-political position for an anti-racist clinic, as well as to indications turned to a political episteme aimed at listening to these populations and the demands of psychological suffering due to situations of racism. Being a black subject in Brazil means being a non-subject, while, on the other hand, whiteness is reflected in the absolute place of the whole, which is not aware of the pain and suffering of the other, because this other is made invisible by racism and sometimes denied and silenced. As a result, we, based on the narratives and theoretical productions raised found, that we can consider that an anti-racist clinic is a concept that is still lacking in Brazilian psychology, as this does not reflect on racism, neither its (institutional) nor that of society (structural), as it should. The psychological clinic is constituted in everyday life still alien to racial issues, when we can take into account that there is a clinic that denies racism. However, we consider that the exception occurs with the black psychologists we found, carrying out this practice in psychology and in the clinic for at least 40 years, being considered here as the classics of psychology, as they perform psychotherapy in an action that considers the narratives on racism and the harms of racism to mental health. We point out that it is necessary to listen to these authors who spoke about the clinic based on the reading of Frantz Fanon, being authors that we define as the counter-hegemonic classics, who bring the theoretical foundation of this thesis: Virgínia Bicudo, Neusa Santos, Lucia da Silva , Isildinha Baptista, Jesus Moura, who already do (and did) an anti-racist clinic, Brazilian and decolonized, therefore decolonial. For an ethical-political commitment, it is necessary to incorporate in psychology the concepts of intersectionality (Caletiva Rio Combahee, krenshaw) and the sociogenic principle (Fanon and Wynter), for a critical and transforming reading of this social reality. We based on decolonial knowledge, found that the way to conceptualize an anti-racist clinic presupposes an ethical position – aesthetic, political, therefore, in a praxis. We point out that the anti-racist clinic should not be carried out only by and for black people, but by all professionals who are racially aware, taking into account black psychotherapists and racial literacy considering the white therapists.